Development of Interview Skills Using Clinical Simulation in Speech-Language Therapy - Aguilar-Fuentealba, Victoria del Pilar; Pérez-Villalobos , Cristhian (Revista Chilena de Fonoaudiología, 2024)
Objective structured clinical evaluation (OSCE) is a type of clinical simulation that has significantly changed how clinical interview skills are developed, specifically regarding anamnesis and communication. However, there is little evidence of its use in speech-language therapy. The purpose of this work was to analyze the use of formative OSCE as a pedagogical strategy to teach clinical interview skills in the second year of a Speech-Language Therapy program. This is a quantitative and analytical-relational study with a quasi-experimental, pre-post design. The sample included 17 students from the Speech Therapy program at Universidad Andres Bello. Clinical interview skills were evaluated using an observation scale and a self- efficacy scale, both before and after the formative OSCE. Three observation guidelines were applied during the interview: anamnesis, clinical judgment, and communication. Finally, students completed a survey on their perception of the OSCE methodology. All participants showed improvements in their clinical interview skills and their levels of self-efficacy. The differences in anamnesis and communication were statistically significant (p<0.05). Similarly, they expressed high levels of satisfaction with the methodology. In conclusion, formative OSCE favors the development of anamnesis and communication competencies in speech-language therapy students, in addition to increasing their self-efficacy in these areas. Furthermore, the participants expressed a high degree of satisfaction with the method.